Kape tayo the revealed comparative advantage of selected Filipino coffee in the global market - Galaura, Allen Grace F.; Samson, Eija Patricia C.
Coffee has long been part of the Philippine socio-cultural landscape and inter- country trade. However, the Department of Trade and Industry has reported that the coffee industry has been experiencing a significant decline in its production level affecting both exports and local supply. This paper hypothesizes that selected Philippine coffee variants still have the potential to be competitive in the global market. Their competitiveness could be measured through computing the Balassa Revealed Comparative Advantage (BRCA) and using regression analysis to know which factors contribute to their variations over time. The results of the Balassa RCA were lower than one, showing that the selected Philippine coffee exports do not have revealed comparative advantage. According to the regression results, the potential to gain comparative advantage lies within the Philippine coffee exports, particularly in 090111 (Coffee; not roasted or decaffeinated) and 090112 (Coffee; decaffeinated, not roasted) coffee variants. The results of the models reinforce each other indicating that directing policies towards the productivity of these exports over time can positively affect how the local coffee sector becomes competitive in the global market.